2005
DOI: 10.1038/sj.bjc.6602760
|View full text |Cite
|
Sign up to set email alerts
|

CA19-9 as a prognostic factor in inoperable pancreatic cancer: the implication for clinical trials

Abstract: In a multivariate analysis of 154 patients receiving chemotherapy, baseline CA19-9 was an independent prognostic factor for overall survival (OS) (HR 1.8; 95% CI: 1.3 -2.5, P ¼ 0.0004). The 1-year OS was 19 and 46%, respectively, for patients with a baseline CA19-9 above or below the median value. A fall of 20% in CA19-9 level from baseline was an independent prognostic factor for OS (HR 1.9; 95% CI: 1.1 -3.4, P ¼ 0.019).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
106
3
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 17 publications
(16 reference statements)
11
106
3
3
Order By: Relevance
“…Whether serum CA 19-9 levels can be used as a surrogate marker of response to chemotherapy has been studied in a variety of clinical settings [41,44,[53][54][55][56][57][58][59][60][61][62][63][64]. Willett et al measured CA 19-9 serum levels in 42 resectable pancreatic cancer patients receiving neoadjuvant treatment with 5-flourouracil and external beam radiation prior to planned pancreaticoduodenectomy.…”
Section: Ca 19-9 Serum Levels As a Biomarker For Chemotherapy Responsmentioning
confidence: 99%
See 3 more Smart Citations
“…Whether serum CA 19-9 levels can be used as a surrogate marker of response to chemotherapy has been studied in a variety of clinical settings [41,44,[53][54][55][56][57][58][59][60][61][62][63][64]. Willett et al measured CA 19-9 serum levels in 42 resectable pancreatic cancer patients receiving neoadjuvant treatment with 5-flourouracil and external beam radiation prior to planned pancreaticoduodenectomy.…”
Section: Ca 19-9 Serum Levels As a Biomarker For Chemotherapy Responsmentioning
confidence: 99%
“…Nearly all studies have demonstrated that a treatment related decline in CA 19-9 serum levels is associated with prolonged survival and is an independent predictor of overall survival [41,44,[53][54][55][56][57][58][59][60][61][62][63][64] (Table 5). Reni et al compared basal CA 19-9 serum levels in 247 advanced pancreatic cancer patients enrolled in five consecutive chemotherapy trials (G, gemcitabine; PEFG, cisplatin, epirubicin, 5-fluorouracil, and gemcitabine; PDXG, cisplatin, docetaxel, capecitabine, and gemcitabine) [60].…”
Section: Ca 19-9 Serum Levels As a Biomarker For Chemotherapy Responsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ln, log; Diff, difference; Wk, week. 0.53; P ¼ 0.019) have been shown to have a superior survival (Maisey et al, 2005). CA19-9 may serve as an early indication of treatment efficacy with cytotoxic drugs, but interpretation of CA19-9 kinetics is more complex with other molecular targeted drugs.…”
Section: Discussionmentioning
confidence: 99%